2019
DOI: 10.1590/1678-4324-2019180133
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness and Ultrastructure of Demineralized Gamma-Irradiated Human Enamel after Diode Laser (980 nm) and Fluoride Surface Treatment

Abstract: were then exposed to demineralizing solution for 72 hours. Examination of slabs was performed using vickers microhardness test and scanning electron microscope; The lowest microhardness was recorded in group G, while inGL and GFL groups it significantly increased. Scanning electron microscope revealed a pronounced loss of central prism core and retention of prism peripheries in group G. Confluence of prismatic and interprismatic structures in GL slabs and irregular rough surface with prismatic boundaries conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…This was demonstrated in the present study by the ESEM, as the irradiated sample showed a merging of both prismatic and interprismatic structures, with distorted prismatic peripheries. This is in agreement with findings by Duruk et al [14], Bakr [21] and Rodrigues et al [31]. Furthermore, this change in the enamel crystalline structure was suggested as one of the factors related to the increased risk of dental caries following radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was demonstrated in the present study by the ESEM, as the irradiated sample showed a merging of both prismatic and interprismatic structures, with distorted prismatic peripheries. This is in agreement with findings by Duruk et al [14], Bakr [21] and Rodrigues et al [31]. Furthermore, this change in the enamel crystalline structure was suggested as one of the factors related to the increased risk of dental caries following radiation therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Windows of 3 mm × 3 mm were made to standardize the area of all specimens in Groups G-L and L-G that were to be exposed to laser irradiation. The periphery of the windows was coated with nail varnish [21]. The enamel specimens were irradiated in the National Institute of Laser-Enhanced Sciences, Egypt, using a diode laser device (Quanta c 980 nm, Italy) at 2 watt for 15 sec, in a continuous and contact modes, using an optic fiber transmission system with a diameter of 320 µm.…”
Section: Diode Laser Irradiationmentioning
confidence: 99%
“…Furthermore, the differences between mean O wt% and C wt% were statistically significant, with decreases recorded in both. Our results assessing the 980 nm diode laser were in agreement with previous studies that have obtained enamel that is less susceptible to acid demineralization due to calcium increases, less-modified phosphorus concentrations, and decreases in carbon and oxygen contents [ 33 , 37 , 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that increases in Ca wt% and P wt% increase the resistance of enamel to dissolution [ 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 33 , 37 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]; however, the mean of oxygen wt% before and after irradiation for both wavelengths were about the same, while that for carbon was lower after irradiation with both lasers. The content of carbon in teeth can be correlated with various factors, such as enamel maturity, dietary intake, caries susceptibility, and the hypoplastic status of the enamel [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This intracrystalline disorder appearing explains the appearance of a spacing between the prisms of HAP as if the structure of the enamel were to crack. The second effect mentioned in literature as a consequence of exposure to gamma radiation of enamel is demineralization [11,21]. This is manifested by loss of HAP prisms from the enamel surface at the nanostructure level (something similar to what it was began to be observed in Figure 2C.c after 6 h of treatment).…”
Section: Discussionmentioning
confidence: 55%